Password-authenticated group key establishment from smooth projective hash functions - Bohli, Jens-Matthias; González Vasco, Maria Isabel; Steinwandt, Rainer (Zielona Góra: Uniwersytet Zielonogórski)
Thus, they can be implemented without complex infrastructures that typically involve public keys and certificates. In this paper, a provably secure password-authenticated protocol for group key establishment in the common reference string (CRS) model is presented. While prior constructions of the group (PAKE) can be found in the literature, most of them rely on idealized assumptions, which we do not make here. Furthermore, our protocol is quite efficient, as regardless of the number of involved participants it can be implemented with only three communication rounds.
Keywords: group key exchange; password authentication; smooth projective hashing